Oxygen and carbon dioxide levels in patients after cardiac arrest. (May 2020) - Peluso, Lorenzo; Belloni, Ilaria; Calabró, Lorenzo; Dell'Anna, Antonio Maria; Nobile, Leda; Creteur, Jacques; Vincent, Jean-Louis; Taccone, Fabio Silvio
Abstract: Background: The relationship of PaO2 and PaCO2 levels with outcome after cardiac arrest (CA) is controversial. Few studies have analysed both PaO2 and PaCO2 in this setting and the overall exposure to different PaO2 and PaCO2 levels has not been taken into account. Methods: We reviewed blood gas data obtained within the first 24 h from all comatose adult patients who were admitted to the intensive care unit after successful resuscitation from CA. Exposure times to different PaO2 and PaCO2 thresholds were reported as areas under the curve (AUC) and the time above these thresholds was then calculated. The primary outcome measure was neurological outcome assessed using the Cerebral Performance Category (CPC) score at 3 months. An unfavourable outcome was defined as a CPC of 3–5 and a favourable outcome as a CPC of 1–2. Results: A total of 356 patients were studied, with a median number of 9 [6–11] blood gas measurements within the first 24 h after admission. The highest and lowest PaO2 and PaCO2 were similar in patients with unfavourable and favourable neurological outcomes. There were no differences in the AUCs or times over different thresholds of PaO2 and PaCO2 in the two groups. In a multivariable analysis, high blood lactate concentrations on admission, presence of shock and a non-shockable initial rhythm were significantly associated with unfavourable outcome. Conclusions: There was no association between exposure to various levels of PaO2 and PaCO2 and neurological outcome after cardiac arrest.